Gender Differences in the Reading Performance of Texas Grade 3 English Language Learners: A Multiyear, Statewide Investigation - Schleeter, Gideon D; Slate, John R; Moore, George W; Lunenburg, Frederick C (Asian Journal of Interdisciplinary Research, 2019)
Analyzed in this investigation were the current Texas state-mandated assessments in reading and the extent to which test scores differed between English Language Learner boys and English Language Learner girls. Data were obtained on the reading performance of all Grade 3 English Language Learner boys and girls for three school years. Inferential statistical analyses revealed that English Language Learner girls had statistically significantly better reading performance than English Language Learner boys in all three school years. Implications for policy and practice, as well as recommendations for future research, are provided.